Do Causes Influence Functional Aspects and Quality of Life in Patients with Nonfibrocystic Bronchiectasis? - Ádria Cristina da Silva; Jessica de Campos Medeiros; Monica Corso Pereira (Pulmonary Medicine)
Background. The denomination of noncystic fibrosis bronchiectasis (NCFB) includes several causes, and differences may be expected between the patient subgroups regarding age, comorbidities, and clinical and functional evolution. This study sought to identify the main causes of NCFB in a cohort of stable adult patients and to investigate whether such conditions would be different in their clinical, functional, and quality of life aspects. Methods. Between 2017 and 2019, all active patients with NCFB were prospectively evaluated searching for clinical data, past medical history, dyspnea severity grading, quality of life data, microbiological profile, and lung function (spirometry and six-minute walk test). Results. There was a female predominance; mean age was 54.7 years. Causes were identified in 82% of the patients, the most frequent being postinfections (n=39), ciliary dyskinesia (CD) (n=32), and chronic obstructive pulmonary disease (COPD) (n=29). COPD patients were older, more often smokers (or former smokers) and with more comorbidities; they also had worse lung function (spirometry and oxygenation) and showed worse performance in the six-minute walk test (6MWT) (walked distance and exercise-induced hypoxemia). Considering the degree of dyspnea, in the more symptomatic group, patients had higher scores in the three domains and total score in SGRQ, besides having more exacerbations and more patients in home oxygen therapy. Conclusions. Causes most identified were postinfections, CD, and COPD. Patients with COPD are older and have worse pulmonary function and more comorbidities. The most symptomatic patients are clinically and functionally more severe, besides having worse quality of life.